1977
DOI: 10.1044/jshr.2001.81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulus Frequency and Intensity on the Middle Components of the Averaged Auditory Electroencephalic Response

Abstract: Middle components (la6tency 8–50 msec) of the averaged auditory electroencephalic response (AAER), evoked by brief duration tone bursts, were recorded from 11 normal-hearing subjects. Latency and amplitude measurements were made on five peaks (N a , P a , N b , P b , and N c ) of the AAER waveforms recorded for 27 experimental conditions: three conditions of stimulus frequency (250, 1000, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…The MLR components were labelled according to their polarity and in alphabetical order (Mendel and Goldstein, 1971;Thornton et al, 1977) even if the latency of the components may make them seem to belong to the slow potentials category (Picton et al, 1974;Picton and Smith, 1978). Wave V of the auditory brainstem response (ABR) and the P wave preceding Na (Picton et al, 1974;Picton and Smith, 1978;Kavanagh et al, 1984) were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…The MLR components were labelled according to their polarity and in alphabetical order (Mendel and Goldstein, 1971;Thornton et al, 1977) even if the latency of the components may make them seem to belong to the slow potentials category (Picton et al, 1974;Picton and Smith, 1978). Wave V of the auditory brainstem response (ABR) and the P wave preceding Na (Picton et al, 1974;Picton and Smith, 1978;Kavanagh et al, 1984) were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16] Our data revealed no difference in latency time variability at the frequencies that were tested (Tab 2). Thornton et al 19 observed decreased latency with increased frequency. The 2000 Hz frequency elicited the highest number of responses except for Pb, which was mostly present at 500 Hz (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of this use include patients with multiple sclerosis, cerebral tumors, epilepsy, traumatic brain injury and learning disabilities. 8 A narrow band stimulus capable of stimulating specific cochlear regions could be used clinically 19 to quantitatively assess hearing loss. In other words, establishing electrophysiological thresholds at a specific frequency would truly be an electrophysiological pure tone audiometry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations